Monetary policy and regional inequality - Sebastian Hauptmeier; Fédéric Holm-Hadulla; Katerina Nikalexi (European Central Bank (ECB), 2020)
We study the impact of monetary policy on regional inequality using granular data on economic activity at the city- and county-level in Europe. We document pronounced heterogeneity in the regional patterns of monetary policy transmission. The output response to monetary policy shocks is stronger and more persistent in poorer regions, with the difference becoming particularly pronounced in the extreme tails of the distribution. Regions in the lower parts of the distribution exhibit hysteresis, consisting of long-lived adjustments in employment and labor productivity in response to the shocks. As a consequence, policy tightening aggravates regional inequality and policy easing mitigates it.
Keywords: C32; E32; E52; 330; monetary policy; regional heterogeneity; local projections; quantile regressions